LITERATUR REVIEW : MODEL EVALUASI CIPP (CONTEXT, INPUT, PROCESS, DAN PRODUCT) DALAM PENDIDIKAN VOKASIONAL - Muhammad Ihsan Hadi Tanoyo (CV. ADIBA AISHA AMIRA, 2024)
Vocational Education is education that prepares students to enter jobs that suit their needs and provides provisions for students to develop their potential. This article aims to provide an understanding of the CIPP evaluation model in Vocational Education. The CIPP model has 4 steps, namely: 1. Context Evaluation, 2. Input Evaluation, 3. Process Evaluation, and 4. Product Evaluation. The implementation of the 2013 Curriculum uses the CIPP (Context, Input, Process, and Product) evaluation model. The CIPP model does not only focus on results, but also context, input, process, and results. Therefore, the CIPP model is said to be more comprehensive than other evaluation models. This research method is a literature review, first analyzed the application of the CIPP model in program evaluation, then analyzed the application of the CIPP model in Vocational Education.